How has early marriage, a critical social determinant of child stunting and wasting, changed over a decade in South Asia? Trends, inequities and drivers, 2005 to 2018 - Scott, Samuel P.; Nguyen, Phuong Hong; Neupane, Sumanta; Pramanik, Priyanjana; Nanda, Priya; Menon, Purnima; Bhutta, Zulfiqar A.; Afsana, Kaosar (American Society for Nutrition, 2020)
In South Asia, many women are married before their 18th birthday and give birth soon after. Delaying marriage is an attractive nutrition policy target as previous research shows that early marriage (EM) is associated with poor child growth outcomes, operating through many pathways. We sought to describe the prevalence, trends, inequities and predictors of EM in South Asia.